Evaluation of germplasm and comparison between pedigree and single descent methods in Yardlong bean (vigna unguiculata ssp. sesquipedalis (L.) Verde) - Teerawat Sarutayophat (Prince of Songkla University, 2010)
Thesis (Ph.D., Plant Science)--Prince of Songkla University, 2008